Kelainan Fisik Tokoh Auggie Dalam Novel Wonder Karya R.J. Palacio - Syadilla Hafsha Puteri Cantika; Saprudin; Siska Hestiana (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2021)
Physical disability can lead to discrimination in the life of a boy who first set an informal school when he was about to start his first class in grade 5 (five), his name is August Pullman in the novel Wonder by R. J. Palacio. This study aims to analyze the depiction of Auggie's character and the interaction of Auggie's character with other supporting characters by using the theory of character according to Abrams and the theory of Alur according to Nurgiyantoro. This research uses a descriptive qualitative research method. Researchers use a social approach to describe the conditions or social interactions contained in the novel. This study describes the description of Auggie's character and the relationship of Auggie's character with other supporting characters and there is a problem with Treacher Collins syndrome, which causes a series of events, conflicts, or climaxes so that the researcher analyzes based on the plot structure.